2020
DOI: 10.1007/s10875-020-00785-8
|View full text |Cite
|
Sign up to set email alerts
|

The Growing Spectrum of Human Diseases Caused by InheritedCDC42 Mutations

Abstract: Several recent studies provide valuable new information that expands the spectrum of human disease associated with mutations in CDC42.CDC42, an intracellular member of the Rho-family GTPases, is a key regulator of cell polarity that is highly conserved among eukaryotes (reviewed in [1]). By regulating the assembly of actin cytoskeletal structures in a temporal-spatial manner, CDC42, along with RAC and RHO A, controls cell shape and cell movement. In this way, CDC42 plays an important role in migration and dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Levels of inflammatory mediators, IL-1β, IL-18, IFN-γ, and CXCL9, are very high in the serum of CDC42-deficient patients, and the constitutive production of these factors by bone marrow cells is also higher in patients than in healthy donors ( Bucciol et al, 2020 ; Gernez et al, 2019 ; Lam et al, 2019 ). Consistent with these observations, treatment with inhibitors of IL-1 or IFN-γ was found to be effective in some cases of CDC42 deficiency ( Gernez et al, 2019 ; Lam et al, 2019 ; Su and Orange, 2020 ). CDC42 deficiency may impair cytotoxic lymphocyte function and promote the production of inflammatory mediators, thereby fueling a cytokine storm.…”
Section: Monogenic Disorders Underlying Virus-triggered Hyperinflammatory Disease: the Example Of Hemophagocytic Lymphohistiocytosis (Hlhsupporting
confidence: 62%
See 1 more Smart Citation
“…Levels of inflammatory mediators, IL-1β, IL-18, IFN-γ, and CXCL9, are very high in the serum of CDC42-deficient patients, and the constitutive production of these factors by bone marrow cells is also higher in patients than in healthy donors ( Bucciol et al, 2020 ; Gernez et al, 2019 ; Lam et al, 2019 ). Consistent with these observations, treatment with inhibitors of IL-1 or IFN-γ was found to be effective in some cases of CDC42 deficiency ( Gernez et al, 2019 ; Lam et al, 2019 ; Su and Orange, 2020 ). CDC42 deficiency may impair cytotoxic lymphocyte function and promote the production of inflammatory mediators, thereby fueling a cytokine storm.…”
Section: Monogenic Disorders Underlying Virus-triggered Hyperinflammatory Disease: the Example Of Hemophagocytic Lymphohistiocytosis (Hlhsupporting
confidence: 62%
“…Mutations of XIAP or NLRC4 dysregulate inflammasome activation, leading to excessive and sustained production of IL-1β, IL-18, and CXCL9 ( Canna and Marsh, 2020 ). Moreover, monoallelic mutations of CDC42 were recently reported to cause multisystemic inflammation, including HLH ( Su and Orange, 2020 ). Levels of inflammatory mediators, IL-1β, IL-18, IFN-γ, and CXCL9, are very high in the serum of CDC42-deficient patients, and the constitutive production of these factors by bone marrow cells is also higher in patients than in healthy donors ( Bucciol et al, 2020 ; Gernez et al, 2019 ; Lam et al, 2019 ).…”
Section: Monogenic Disorders Underlying Virus-triggered Hyperinflammatory Disease: the Example Of Hemophagocytic Lymphohistiocytosis (Hlhmentioning
confidence: 99%
“…In some cases, these functions go well beyond what may have been expected or anticipated based on animal models (e.g., TBX21 [ 25 ]). They have also already highlighted the heterogenous phenotypes that can result from variants in the same gene (e.g., CDC42 [ 33 39 , 52 ]), indicated that significant diseases can arise from mono-allelic or bi-allelic loss of function ( IL6ST [ 9 ], RIPK1 [ 42 , 43 ]) or bi-allelic loss- or gain-of-function ( CEBPE [ 24 ], STAT2 [ 40 , 41 ]) variants in the same gene, or from autoAb phenocopies of monogenic lesions (e.g., COVID19 and anti-IFN Abs) [ 48 ], and identified novel somatic mutations as pathogenic causes of immune disorders ( UBA1 ) [ 47 ]. Importantly, they have also provided opportunities for therapeutic interventions, such as JAK inhibitors to treat STAT2 gain of function [ 40 , 41 ] or SOCS1 deficiency [ 22 ], IFNγ to treat mycobacterial disease [ 25 , 26 ], or early IFN-β or IFN-α2a treatment of SARS-CoV2 infection in COVID-19 patients with autoantibodies against IFN-α or IFN-ω [ 67 ] or impaired type 1 IFN responses [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“… Abbreviations : AR , autosomal recessive; AD , autosomal dominant; AID , activation-induced cytidine deaminase; CSR , class switch recombination; SHM , somatic hypermutation; MDS , myelodysplastic syndrome; LOE , loss of expression; LOF , loss of function; GOF , gain of function; DN , dominant negative; MSMD , Mendelian susceptibility to mycobacterial disease; HLH , hemophagocytic lymphohistiocytosis; FTT , failure to thrive; hPSC , human pluripotent stem cells; iPSC , induced pluripotent stem cells; CMV , cytomegalovirus • Not all Tables in the 2020 classifications [ 2 , 3 ] are listed in the “Table” column because not all Tables are represented by the new variants detailed above • Mutations in PAX1 previously reported to cause OTFCS2 (but CID/SCID not reported) [ 49 ] • Variants in IL6ST have been previously listed to cause an IEI due to recessive partial LOF alleles [ 50 ] • Dominant-negative mutations in IL6ST all target the intracellular domain of gp130, truncating the STAT3 binding sites as well as recycling motif, leading to sustained expression of a dead receptor (as opposed to recessive alleles, when detected in heterozygous carriers are benign) • Fnip1 ko mice also previously reported [ 12 , 13 ]; humans very similar • Variants in CEBPE have been previously listed to cause an IEI due to recessive LOF alleles [ 51 ] • Mutations in CDC42 previously identified in individuals with neurodevelopmental delay (Takenouchi-Kosaki syndrome) [ 52 ]; in these patients with autoinflammation and CDC42 mutations no such features were noted, except mild facial dysmorphism in some [ 33 39 ] .• Variants in STAT2 have been previously listed to cause an IEI due to recessive LOF alleles [ 53 , 54 ] • The same amino acid was found to be affected (R148Q/W) for both families affected by STAT2 GOF [ 53 , 54 ] • Variants in RIPK1 have been previously listed to cause an IEI due to recessive LOF alleles [ 55 , 56 ]; the heterozygous dominant mutations in RIPK1 reported here all affect the D324 amino acid residue that is important for cleavage …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation